Using the CRISPR/Cas9 system to understand neuropeptide biology and regulation. (August 2017) - Hay, Elizabeth A.; Knowles, Christopher; Kolb, Andreas; MacKenzie, Alasdair
Abstract: Neuropeptides and their receptors play a role in physiological responses such as appetite, stress and inflammatory pain. With neuropeptides having such diverse and important physiological roles, knocking-out the genes encoding them, their receptors, parts of their regulatory sequences, or reproducing disease associated polymorphic variants are important steps in studying neuropeptides and how they may contribute to disease. Previously, knock-outs were generated using methods such as targeted homologous recombination in embryonic stem cells but this method is costly and time-consuming. The CRISPR/Cas9 system has rapidly taken over the genome editing field and will advance our understanding of neuropeptide genes and their regulation. With CRISPR/Cas9 technology, the time and costs involved in producing transgenic animal models, is greatly reduced. In this review, we describe how the system can be used to manipulate genomic sequences by "knock-out" or "knock-in" mutations in cell lines or in animal models. We also discuss the specificity of the system and methods to limit off-target effects. When combined with the availability of genome sequences, CRISPR/Cas9 directed genome editing in vitro and in vivo, promises to provide a deeper understanding of the biology of the neuropeptides in health and disease than has ever been available before. Highlights: The CRISPR/Cas9 system is set to advance our understanding of neuropeptide genes. The CRISPR/Cas9 system allows for efficient genome editing. Knock-out mutations can be produced more efficiently than knock-in mutations. Off-target effects of CRISPR/Cas9 can be controlled using different strategies.